Social protection and local government in Ethiopian private organization: the case of Ayehu and Birshelko privatized farm workers (Revista de Investigaciones Universidad del Quindío, 2022)
This paper tried to investigate the social protection dimension in terms of the nature of citizenship and local government among the workers of Ayehu and Birshelko privatized farm investments in Amhara National Regional State of Ethiopia. Methodologically, a mixed research approach with a sequential exploratory design was used, whereby qualitative data was first collected, followed by quantitative data. Such methods of data collection as interviews, focus group discussions, observation, document review and questionnaires were employed to gather empirical data. Accordingly, the study found out that the workers in these two farms are organized under a kebele government administrative structure, just like other citizens of Ethiopia; they obtain some governmental services and social provisions. However, the workers also face serious challenges by virtue of being located on farms that are delinked from the neighboring rural communities, and they are at the periphery concerning basic government services. These predicaments basically emerge from the structural fault lines of kebele administrative logic and the lack of proper implementation of the citizenship rights as stipulated in the constitution.